Credence goods in the literature: What the past fifteen years have taught us about fraud, incentives, and the role of institutions - Loukas Balafoutas; Rudolf Kerschbamer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We review the literature on credence goods since Dulleck and Kerschbamer (Journal of Economic Literature 44(1), 5-42, 2006). We consider various markets for credence goods and briefly discuss evidence on the extent of fraud. We then review theoretical and empirical contributions on the determinants of seller and consumer behavior in markets for credence goods. The topics include informational asymmetries, pro-social motivations and seller characteristics, as well as several features of the market structure and institutional environment (separation of diagnosis and treatment, liability, verifiability, reputational concerns, competition between experts and second opinions). We also describe recent developments in this area of research (such as the role of investing in more precise diagnostic technologies) and offer an outlook on future questions.
Keywords: D82; D83; D21; D22; D18; I11; L15; 330; Credence Goods; Expert Services; Fraud; Undertreatment; Overtreatment; Overcharging